Análise do processo de ensino e de aprendizagem no ciclo profissionalizante do curso de odontologia da UFES : percepção de docentes e estudantes - Farias, Cynthia Moura Louzada (2015)
Introduction Classroom routine in higher education institutions is a field of work that constantly encourages studies, investigations and research towards a more prospective learning processes, not only students', but also professors' learning processes. Objective: This study aims at carrying out an exploratory, descriptive and explanatory investigation so as to analyze and describe the teaching-learning process in the professionalizing cycle of the Dentistry Program at the Federal University of Espírito Santo (UFES), Brazil, from the perception of students and teachers. Methodology: It is a quanti-qualitative, exploratory, descriptive and explanatory study. The sample comprised 60 professors at the professionalizing cycle departments of the Dentistry Program at UFES and students of the 7th and 10th term in the course. A semi-structured questionnaire and interview, based on Lazzarin (2005), Araújo a M ll (2011) C J ’(2008) instruments were employed in this study. The project was approved by the Research Ethics Committee CCS/UFES under registration no. CAAE 339550144.0000.5060. Descriptive statistical analysis (percentage rate) was performed using Statistical Package for Social Science for Windows (SPSS) and qualitative data (interview) were interpreted based on Bardin content analysis studies (2009). The variables analyzed were: teacher training; planning of lessons developed by teachers; interaction with students; needs work done by teachers; perceived difficulties in the work of the teachers; more effective learning experiences for students and students' attention in the lectures. Results: P ’ p l how that 91.1% of them hold an advanced postgraduate degree (doctorate) and 75.6% have had pedagogical training at some point of their postgraduate programs. The option for teaching was programmed by 91.1% of them, in which 77.8% worked as full-time professors. Data show that over 50% of participant professors have administrative, research/extension activities, besides their classroom work hours. The social-dental care needs in Brazil are understood by 95.6% of professors, and 51.1% of them believe that graduated professionals leave the course prepared to meet the l h B z l . I ’ p , h g q l y the Dentistry Program at UFES is rated as excellent by 43.6%, and most of them are satisfied (50.4%) with the graduate program, but feel discouraged by some facts. Practice classes were the most effective aspect by 50.4% among students. Among the professors interviewed, there is clear interest in participating by 91,1% in incorporated professional development programs to improve their teaching skills. Conclusion: In conclusion, the professor of dentistry course need to wake up to the need to reflect on their practices, because it continues favoring technical knowledge at the expense of teaching. Dentistry students show difficulties in demonstrating social sensitivity and concern for the problems of the population. The study is intended to alert the postgraduate courses of higher education institutions on the need to seek alternatives to qualify the professionals who make up the teaching staff of the institutions, which do not have adequate training for teachers. In the medium term, we plan to use data from this study to approach strategies and an intervention project, that allow improving the teaching-learning process and consequent background of students graduated in the Dentistry Program at UFES that positively impact the health care.